2007
DOI: 10.1080/08977190801886905
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of proIGF-II and IGF-II on resveratrol induced cell death by regulating survivin cellular localization and mitochondrial depolarization in breast cancer cells

Abstract: Insulin-like growth factor II (IGF-II) plays a pivotal role in fetal and cancer development by signaling through the IGF-I and insulin receptors and activating the estrogen signaling cascade. We previously showed that precursor IGF-II (proIGF-II, the predominant form expressed in cancer) and not mature IGF-II (mIGF-II) blocks resveratrol (RSV) (a phytoalexin/anticancer agent)-induced cell death in MCF-7 cells. We hypothesize that proIGF-II regulates antiapoptotic proteins and/or the mitochondria to inhibit RSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Of significance, IGF-II expression and regulation of Bcl-XL and Survivin in cell lines correlated with their expression in paired breast tissues. We also demonstrated that IGF-II siRNA treatment or IGF-II stable antisense transfection completely inhibited Survivin expression in breast cancer cells (Kalla Singh et.al., 2008). Both, cell lines and paired breast tissues from AA patients expressed significantly higher levels of Survivin than their CA counterparts (Kalla Singh et.al., 2010a).…”
Section: Discussionmentioning
confidence: 86%
“…Of significance, IGF-II expression and regulation of Bcl-XL and Survivin in cell lines correlated with their expression in paired breast tissues. We also demonstrated that IGF-II siRNA treatment or IGF-II stable antisense transfection completely inhibited Survivin expression in breast cancer cells (Kalla Singh et.al., 2008). Both, cell lines and paired breast tissues from AA patients expressed significantly higher levels of Survivin than their CA counterparts (Kalla Singh et.al., 2010a).…”
Section: Discussionmentioning
confidence: 86%
“…IGF-II is a potent mitogen associated with increased cancer cell survival, proliferation [10], and an elevated risk of breast cancer recurrence [11]. We have previously demonstrated that IGF-II regulates the anti-apoptotic proteins Bcl-2, Bcl-X L and survivin in the ER (+) MCF-7 breast cancer cell line, leading to inhibition of mitochondrial membrane depolarization, cell survival and chemoresistance [7, 8]. These findings prompted us to study the effects of IGF-II (mature and precursor forms), and IGF-II siRNA on the expression of Bcl-2, Bcl-X L and survivin in AA and CA breast cancer cells and analyzing how it compares to IGF-II and the anti-apoptotic proteins expression in breast tissue samples from AA and CA women.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that IGF-II regulates the anti-apoptotic proteins survivin, Bcl-2 and Bcl-X L in MCF-7 (CA, ER+) breast cancer cells. These survival proteins inhibit mitochondrial membrane depolarization and prevent cell death [7, 8]. We demonstrated that the precursor form of IGF-II (proIGF-II) was more potent than mature IGF-II (mIGF-II) in up-regulating these proteins through increased phosphorylation of IRS-1 at tyrosine 632, which subsequently binds SH2 domains in the p85 regulatory subunit of PI3K [8].…”
Section: Introductionmentioning
confidence: 99%
“…Both the related growth factors insulin and IGF1 have been implicated in prostate cancer (PC) progression (Pollak 2008a, Lubik et al 2011; however, the role of IGF2 is less well explored. IGF2 expression is elevated in ovarian, colorectal and breast cancer associated with poor prognosis (Cardillo et al 2003, Sayer et al 2005, Kalla Singh et al 2007, Pollak 2008a, Huang et al 2010 and increased cell motility (Diaz et al 2007). Dysregulated expression of IGF2 in PC tumours and in surrounding prostate and stromal tissue occurs partially through loss of imprinting (Van Roozendaal et al 1998, Cui et al 2003, Poirier et al 2003, Bhusari et al 2011, Wang et al 2011 and correlates with tumour vs benign hyperplasia (Paradowska et al 2009); however, tumour IGF2 expression levels are not reflected in serum (Rowlands et al 2009(Rowlands et al , 2012.…”
Section: Introductionmentioning
confidence: 99%